2021
DOI: 10.1136/annrheumdis-2021-219969
|View full text |Cite
|
Sign up to set email alerts
|

circPDE4B prevents articular cartilage degeneration and promotes repair by acting as a scaffold for RIC8A and MID1

Abstract: ObjectivesCircular RNAs (circRNAs) have emerged as significant biological regulators. Herein, we aimed to elucidate the role of an unidentified circRNA (circPDE4B) that is reportedly downregulated in osteoarthritis (OA) tissues.MethodsThe effects of circPDE4B were explored in human and mouse chondrocytes in vitro. Specifically, RNA pull-down (RPD)-mass spectrometry analysis (MS), immunoprecipitation, glutathione-S-transferase (GST) pull-down, RNA immunoprecipitation and RPD assays were performed to verify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 45 publications
3
51
1
Order By: Relevance
“…The mechanism of action of circRNA is also complex and diverse. CircRNAs can be used as scaffolds for the assembly of protein complexes [ 7 ]; circRNAs can regulate gene transcription and RNA splicing [ 8 ]; circRNAs containing internal ribosome entry site elements and open reading frames can also be translated into proteins or polypeptides [ 9 ]. However, the most common mechanism of action of circRNA in cancer is the competitive endogenous RNA (ceRNA) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of circRNA is also complex and diverse. CircRNAs can be used as scaffolds for the assembly of protein complexes [ 7 ]; circRNAs can regulate gene transcription and RNA splicing [ 8 ]; circRNAs containing internal ribosome entry site elements and open reading frames can also be translated into proteins or polypeptides [ 9 ]. However, the most common mechanism of action of circRNA in cancer is the competitive endogenous RNA (ceRNA) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups have shown that circRNAs are capable of encoding polypeptides that serve as scaffolds for certain proteins to exert their regulatory effects ( Li et al, 2021 ; Liu et al, 2021 ; Shen et al, 2021 ). We examined the protein coding potential of the bone fide polypeptides of circ0007360 and found that the coding probabilities of them are rather low (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK and phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT) were identified by the bioinformatic analysis as the key pathways involved in the crosstalk between arctiin and OA. Cumulative evidence indicates that abnormal activation of p38-MAPK accelerates articular cartilage degeneration [ 36 ]. Due to the thorough inhibition of arctiin on MAPK or PI3K/AKT [ 33 ], the robust cartilage protection observed in vivo may be mediated in part by these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%